REVIEW OF LEGAL CERTAINTY OF ROYALTY COLLECTION ON MUSIC AND/OR SONGS: A COMPARATIVE STUDY OF INDONESIA AND RUSSIA - Febrian, Muhammad Naufalurridho; Setyawati, Ria; Noventri, Ardhana; Mahendra, Yusril (Realism: Law Review, 2025)
Copyright protection is one of the constitutional rights related to intellectual property, including copyrights on music and/or songs. Under the Copyright Law, royalties are recognized as compensation for the use of the economic rights of a creation. This study focuses on performing rights royalties, which require any person using songs and/or music for commercial purposes in public services to pay royalties to the creators through the National Collective Management Organization (LMKN). However, in practice, the collection of royalties remains problematic, particularly regarding the definition of "commercial user." The ambiguity in the Copyright Law and the Government Regulation on Royalties leads to uncertainty in determining whether the singer or the event organizer is responsible for royalty payments, resulting in a shift of responsibility between parties. On the other hand, a court ruling granted the lawsuit of a songwriter against a singer for performing rights in a concert, despite the legal framework suggesting that royalty payments should be made by the commercial user through LMKN. This study uses a normative legal research method with statutory, conceptual, and case approaches to examine the concept of royalty collection in Indonesia and the legal protection for songwriters, while highlighting the need for legal certainty and regulatory clarity. Keywords: [Music and/or Songs, Intellectual Property Rights, Royalties, Copyright, and Legal Certainty]